"Upside down" reversal of vision after third ventriculostomy - (:unkn) unknown (My University, 1990)
Upside-down reversal of vision is a very rare kind of visual illusion characterized by the upside-down appearance of all objects within the visual field. Only seven cases have been reported since its description. In this paper, we report a case of upside-down reversal of vision, which occurred following a third ventriculostomy operation for hydrocephalus. This is the first case reported in the literature after a surgical intervention. © Williams & Wilkins 1990. All Rights Reserved.
Keywords: Hydrocephalus; Third ventriculostomy; Upside down reversal of vision